Cervical cancer screening and treatment of cervical intraepithelial neoplasia in female sex workers using “screen and treat” approach - Joshi S; Kulkarni V; Darak T; Mahajan U; Srivastava Y; Gupta S; Krishnan S; Mandolkar M; Bharti AC (Dove Medical Press, 2015)
Smita Joshi,1 Vinay Kulkarni,2 Trupti Darak,2 Uma Mahajan,1 Yogesh Srivastava,3 Sanjay Gupta,3 Sumitra Krishnan,1 Mahesh Mandolkar,2 Alok Chandra Bharti31Hirabai Cowasji Jehangir Medical Research Institute (HCJMRI), Jehangir Hospital Premises, Pune, Maharashtra, India; 2Prayas Health Group, Amrita Clinic, Pune, India; 3Institute for Cytology and Preventive Oncology, Indian Council of Medical Research, New Delhi, IndiaObjective: Female sex workers (FSWs) are at an increased risk of human immunodeficiency virus (HIV) as well as human papillomavirus (HPV) infections and thus have an increased risk of cervical intraepithelial neoplasia (CIN) and cervical cancer. We evaluated the feasibility of “screen and treat approach” for cervical cancer prevention and the performance of different screening tests among FSWs.Methods: Women were screened using cytology, VIA (visual inspection with acetic acid), and VILI (visual inspection with Lugol’s iodine) and underwent colposcopy, biopsy, and immediate treatment using cold coagulation, if indicated, at the same visit.Results: We screened 300 FSWs of whom 200 (66.67%) were HIV uninfected and 100 (33.34%) were HIV infected. The overall prevalence of CIN 2–3 lesions was 4.7%. But all women with CIN 2–3 lesions were HIV infected, and thus the prevalence of CIN 2–3 lesions in HIV-infected FSWs was 14/100 (14%, 95% confidence interval: 7.2–20.8). All of them screened positive by all three screening tests. Cold coagulation was well tolerated, with no appreciable side effects.Conclusion: Cervical cancer prevention by “screen and treat” approach using VIA, followed by ablative treatment, in this high-risk group of women is feasible and can be implemented through various targeted intervention programs. Keywords: cytology, VIA, VILI, CIN, cold coagulation, cervical cancer, HPV, FSWs